(untitled) (Journal of Pharmaceutical Negative Results, 2015)
Aim: The Present study is to investigate the antimycobacterial activity of pyrazoline,phenyl pyrazoline and isooxazoline moiety containing lupeol. The main purpose toshow insignificant antimicrobial activity of these lupeol derivatives and hence thatfurther researchers do not waste time to investigate antitubercular activity of thesegroup containing lupeol derivatives. Materials and Methods: Lupeol has beenisolated from Crataeva nurvala and its reported antitubercular activity promptedto prepare semisynthetic derivatives to know how much they show antitubercularactivity. Newer substituted derivatives of lupeol were synthesized by firstly oxidationof lupeol to lupeol aldehyde followed by replacement of aldehydic group by variousgroups as pyrazoline, phenyl pyrazoline and Isooxazoline. These Pyrozoline, Phenylpyrazoline and Isooxazoline derivatives are synthetic analogues of the naturally occurringtriterpenoid lupeol from the plant crataeva nurvala, were tested for their spectral dataand conformation of the groups, then tested these derivatives of lupeol for antitubercularactivity against Mycobacterium tuberculosis (MTB) strain H37Rv using the MicroplateAlamar Blue Assay. Result: The result indicate that pyrazoline, Phenyl pyrazoline andIsooxazoline moiety containing lupeol derivatives did not show antimycobacterialactivity against MTB at 50 µgm/ml. Conclusion: Pyrazoline, Phenyl pyrazoline andIsooxazoline derivative of lupeol did not have significant antimycobacterial activity.Thus, further optimization of it is needed.